Is Kidney Stone Associated with Thyroid Disease? The United States National Health and Nutrition Examination Survey 2007-2018 - Xue, Wenya; Xue, Zihan; Liu, Yanbing; Yin, Pan; Liu, Luyu; Qu, Shen'ao; Wu, Shaobo; Yang, Chuance (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Background: Kidney stones and thyroid disease are two common diseases in the general population, with multiple common risk factors. The associations between kidney stones and thyroid disease are unclear. Aim: This study aims to assess the association between ‘once had a thyroid disease’ and the odds of kidney stones. Methods: Adult participants from the National Health and Nutrition Examination Survey (NHANES) 2007-2018 with reliable kidney stone and thyroid disease data were included. Adjusting for age, gender, race, education level, and marital status, diabetes, hypertension, gout, angina pectoris, stroke, and asthma, logistic regression was used to examine the relationship between kidney stones and thyroid illness. Results: Using stratified analysis, the association between thyroid illness and kidney stones was investigated further. Among the participants, 4.9% had kidney stones, and 10.1% had thyroid disease. Kidney stone was associated with thyroid disease (OR=1.441, (95% CI:1.294-1.604), p <0.01), which remained significant (OR=1.166, (95% CI:1.041-1.305), p <0.01) after adjustments with age, gender, race, education level and marital status, diabetes, hypertension, gout, angina pectoris, stroke, and asthma. Stratified by blood lead, blood cadmium, and blood urea nitrogen levels in the human body, the odds of kidney stones still increased with once having a previous thyroid disease. Conclusions: In this large nationally representative survey over 10 years, kidney stone was strongly associated with thyroid disease. In this cross-sectional study, we explored the association between thyroid disease and kidney stones, which may help clinicians intervene in them early.
Keywords: thyroid disease